Do Psychopathic Traits Distinguish Trajectories of Gang Membership?. (September 2019) - Carson, Dena C.; Ray, James V.
Prior work that examines different stages of gang membership (joining, time in gang, and leaving) indicates that the gang experience is unique to each individual member. However, we know little about what accounts for variations in the gang experience; particularly, with regard to the role of individual-level characteristics. This article helps to fill this gap by examining how trajectories of gang membership vary based on one multifaceted individual-level characteristic: psychopathy. Some prior work suggests that gang members high in psychopathic traits are attracted to gang life and more likely to hold leadership roles in the gang. Other work indicates that those high in psychopathy are not well suited for gang membership. We make use of the Pathways to Desistance data and group-based trajectory modeling to examine these relationships. Results indicate that the relationship between psychopathy and gang membership is dependent upon the distinct factors of psychopathy.